(untitled) (Modern American Journal of Biological and Environmental Sciences, 2026)
Virtual laboratories have become an important innovation in biology education by providing students with interactive digital environments for conducting experiments. This theoretical article examines the educational value of virtual laboratories in teaching experimental biology concepts. Based on existing literature and educational theories, the study explores their impact on conceptual understanding, student engagement, accessibility, and scientific reasoning. The analysis shows that virtual laboratories improve students’ understanding of complex biological processes through visualization and interactive learning.